Are there Business Cycles beyond GDP? Alternative Measures to GDP at Business Cycle Frequencies - Philip Maschke; Jörg Döpke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We discuss properties of alternatives or complements to GDP as a measure of welfare at business cycle frequencies. We argue that these figures are not useful to measure the welfare costs of business cycles. First, data is not available at an appropriate quality and frequency. Second, since the suggested time series sometimes correlate negatively with each other composite indices will lead by construction to very low welfare costs of business cycles. Third, cross-section and quasi-panel evidence based on different samples of countries reveals no impact of the stance of the business cycle on some suggested welfare measures.
Keywords: D60; E32; I31; 330